Climacteric syndrome in women with diabetes mellitus - Olga Rafael'evna Grigoryan (Endocrinology Research Centre, 2013)
Climacteric syndrome in women with glycemic disorders is known to have several unique features, including earlier onset in women with type 1 diabetes mellitus (usually at the age of 46?48 years). However, diabetes mellitus is not a contraindication for hormone replacement therapy (HRT), though the appropriate age for its introduction should be determined on a case-by-case basis.